2020
DOI: 10.1101/2020.01.21.914549
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Candida albicans exhibits distinct cytoprotective responses to anti-fungal drugs that facilitate the evolution of drug resistance

Abstract: We developed a modified protocol for nanolitre droplet-based single cell sequencing appropriate for fungal settings, and used it to transcriptionally profiled several thousands cells from a prototrophic Candida albicans population and several drug exposed colonies (incl. fluconazole, caspofungin and nystatin). Thousands of cells from each colony were profiled both at early and late time points post-treatment in order to infer survival trajectories from initial drug tolerance to drug resistance. We find that pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 79 publications
0
6
0
Order By: Relevance
“…We then constructed a nanoliter droplet-based system modified from Macosko et al using homemade components as described by Boogeshagi et al (Booeshaghi et al, 2019) to reduce the cost of both the device and each population assay. The profiles reported here combine our preliminary effort (Bettauer et al, 2020) with two additional batches of samples with complementary data and analyses to provide better power to examine the technical and biological efficacy of our system. C. albicans populations were grown in rich media alone (untreated, UT) or with an antifungal compound: fluconazole (FCZ), caspofungin (CSP), or rapamycin (RAPA) (Figure 1A -figure supplement 1A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We then constructed a nanoliter droplet-based system modified from Macosko et al using homemade components as described by Boogeshagi et al (Booeshaghi et al, 2019) to reduce the cost of both the device and each population assay. The profiles reported here combine our preliminary effort (Bettauer et al, 2020) with two additional batches of samples with complementary data and analyses to provide better power to examine the technical and biological efficacy of our system. C. albicans populations were grown in rich media alone (untreated, UT) or with an antifungal compound: fluconazole (FCZ), caspofungin (CSP), or rapamycin (RAPA) (Figure 1A -figure supplement 1A).…”
Section: Resultsmentioning
confidence: 99%
“…Only two high-throughout (10 3 to 10 4 cells) fungal transcriptome studies have been conducted in S. cerevisiae including Jackson and colleagues who profiled ~40K S. cerevisiae cells with the commercial Chromium (10X Inc.) system (Dohn et al, 2022;Jackson et al, 2020;Jariani et al, 2020). Our previous effort was the first to profile C. albicans with sc-technologies (Bettauer et al, 2020); in this study we extend and refine the data and analysis that was generated using our fungal nanoliter droplet-based assay (DROPseq), modified from the original system presented by . Our system addresses technical challenges that arise in the fungal setting and provides a flexible cost-effective solution.…”
Section: Introductionmentioning
confidence: 99%
“…One evolutionary advantage to phenotypic resistance is that, theoretically, it can ‘buy time’, which would provide the cell with an opportunity to acquire genetic lesions that confer true resistance, thus maximizing an organism’s survival. Indeed, the adaptation to anti-fungal drugs might be initially attributed to a phenotypic switch to a less drug-susceptible state, which subsequently leads to acquired resistance ( Figure 2 ) [ 85 ]. Although experimental evidence is currently lacking to support this hypothesis in Candida spp., such a combined epigenetic and genetic model of acquired drug resistance is clearly evident in tumor cells [ 86 ].…”
Section: Candida Spp Phenotypic Plasticity Andmentioning
confidence: 99%
“…The most direct way to identify the molecular underpinnings of phenotypic resistance is through single-cell analysis, in order to characterize population heterogeneity at the level of metabolism, physiology, and transcription [ 89 ]. One such study has employed DROPseq technology [ 90 ] to monitor the single-cell transcriptome of C. albicans when exposed to anti-fungal drugs at concentrations below the MIC [ 85 ]. These authors found that the population divided into two distinct groups after 48 h, due primarily to mounting different expression profiles of stress response genes.…”
Section: Candida Spp Phenotypic Plasticity Andmentioning
confidence: 99%
See 1 more Smart Citation